Measurement of thermospheric temperatures using OMTI Fabry-Perot interferometers with 70-mm etalon - Y. Nakamura (2018)
© The Author(s) 2017. Fabry-Perot interferometer (FPI) is an instrument that can measure the temperature and wind velocity of the thermosphere through observations of airglow emission at a wavelength of 630.0 nm. The Solar-Terrestrial Environment Laboratory/Institute for Space-Earth Environmental Research, Nagoya University, has recently developed four new ground-based FPIs. One of those FPIs, possessing a large-aperture etalon (diameter: 116 mm), was installed in Tromsø (FP01), Norway, in 2009. The other three small FPIs, using 70-mm-diameter etalons, were installed in Thailand (FP02), Indonesia (FP03) and Australia (FP04) in 2010-2011. They use highly sensitive cooled-CCD cameras with 1024 x 1024 pixels to obtain interference fringes. However, appropriate temperature has not been obtained from the interference fringes using these new small-aperture FPIs. In the present study we improved the analysis procedure of temperature determination using these FPIs. Each of FPIs measures north, south, east and west directions repeatedly by rotating two mirrors mounted on top of the FPI. We estimated center pixel of laser fringe and airglow fringes for each direction and found significant differences in the center pixel locations (a few pixels) among the measurement directions. These differences are considered to be caused by movement of the scanning mirror on the top of the optics, resulting in mechanical distortion of the optics body. By calculating the fringe center separately for each direction, we could correct these center pixel variations and determine the temperature with random errors of 10-40 K. This new method was employed to the all measurements from four FPIs after 2009 and provided temperatures with reasonably small errors. However, we found that temperatures below 400 K were obtained associated with weak airglow intensities and concluded using a model calculation that they are due to contamination of OH line emissions in the upper mesosphere. By defining an appropriate threshold of the fringe peak count, we successfully eliminated these unrealistic temperature values, and the corrected temperature values became comparable to those provided by the MSIS-90E and GAIA models.